Pearlmillet (Pennisetum glaucum) - wheat (Triticum aestivum) cropping sequence as influenced by cultural, nutritional and irrigation factors under limited moisture conditions - MEENA, B S; GAUTAM, R C; KAUSHIK, S K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted for 2 years during 1993-95 on pearl millet-wheat cropping sequence as influenced b) cultural, nutritional and irrigation factors under limited moisture condition factors. The first crop of the sequence, ie pearlmillet (Pennisetum glaucum (L.) R. Br. emend Stuntz) was grown in kharif 1993 and 1994, and wheat (Triticum aestivum L. emend Fiori & Paol.) was grown thereafter in rabi season of 1993-94 and 1994-95. The strip-plot design with 3 replications was followed keeping all factors of pearlmillet in main plots and irrigation levels to wheat in strip plots. The studies brought out that rainfed conditions are quite favourable for the crop of pearl millet and higher yields are obtained if ’Pusa 322’ hybrid is sown at normal date and fertilized with 40 kg N/ha. Studies further showed that these treatments failed to show any residual effect on the succeeding crop of wheat. Two irrigations were found to be superior to 1 and no irrigation treatment. Total productivity and gross return were also higher in the treatments.